Ebla - Matthiae, Paolo, author.
1 online resource (xxviii, 451 pages)
Keywords: "In Ebla, Paolo Matthiae presents the results of 47 years of excavations at this fascinating site, providing a detailed account of Ebla's history and archaeology. Ebla grew from a small Early Bronze Age settlement into an important trading and political centre, which endured until its final destruction in c.1600 BC. The destruction of its royal palace c.2300 BC was particularly significant as it preserved the city's rich archives, offering a wealth of information on its history, economy, religion, administration and daily life. The discovery of Ebla is a pivotal moment in the history of archaeological investigations of the 20th century, and this book is the result of all the excavation campaigns at Tell Mardikh-Ebla from 1964 until 2010, when field operations stopped for the war in Syria. Available for the first time in English, Ebla offers a complete account of one of the largest pre-classical urban centres by its discoverer, making it an essential resource for students of Ancient Near Eastern archaeology and history"--